Towards an Open Source-First Praxis in Libraries. - McIlwain, J. Robertson (Information Technology & Libraries, 2023)
In terms of utility and technical quality, open-source software solutions have become a common option for many libraries. As barriers to adoption have been reduced and systems such as FOLIO appear poised to change the landscape of LIS technology, it is worth examining how the use of open source can support the normative core values of librarianship and to outline a strategy for critical engagement with the technology that is beneficial to patrons and libraries. Such a strategy will require further codification, institutionalization, and investigation of open source at many levels.